Dampak Pelaporan Keberlanjutan Terhadap Kinerja Dan Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Industri Barang Konsumsi Sub Sektor Makanan Dan Minuman Di BEI Tahun 2022) - Fitriya, Nur Rohmatul; Putri, Nadia Novita Alifiah; Rahmalia, Afifah Yusfi; Pandin, Maria Yovita R (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The purpose of this study was to determine the effect of sustainability reports on company performance and value. The Company's main objective is to generate revenue and improve the welfare of all stakeholders by pursuing a number of profit maximization strategies. However, company management must consider other factors besides the company's current strong financial performance. The business is to strengthen its environmental, social and economic pillars. This study was conducted to ascertain the impact on the performance and value of Consumer Goods Industry Manufacturing Companies in the disclosure of economic, environmental, and social performance in sustainability reporting. A purposive sampling technique was used for the sampling process and data regression analysis was used for the analysis. This study reveals that the company performance of PT Garudafood Putra Putri Jaya Tbk, PT Indofood Sukses Makmur Tbk, and PT Ultrajaya Milk Industry and Trading Company Tbk is significantly affected by the disclosure of environmental performance. In addition, the performance and value of Consumer Goods Industry Manufacturing companies are significantly influenced by the disclosure of economic, environmental, and social performance simultaneously.